Lifetime Multiple Mild Traumatic Brain Injuries Are Associated with Cognitive and Mood Symptoms in Young Healthy College Students - Vynorius, Kyle C.; Paquin, Alyssa M.; Seichepine, Daniel R. (Frontiers in Neurology, 2016)
Background/Objectives: Repetitive mild traumatic brain injury (mTBI; also known as concussion) has been associated with a range of long-term mood and cognitive deficits, including executive dysfunction. Previous research in athletes suggests that cognitive and mood problems are associated with a history of repetitive mTBI. However, to date no studies have examined the impact of a lifetime accumulation of repetitive mTBIs on cognition, particularly executive functioning, and mood in a sample of young adults who were not athletes. Therefore, the present study looked at potential effects of repetitive mTBIs on self-reported cognitive complaints, executive functioning and mood in young adults. Methods: Eighty-four total students responded, and twenty-six of those were excluded from analyses due to reporting only 1 mTBI. The final sample consisted of 58 healthy young adults (mean age = 22.84, STD = 4.88) who completed the Cognitive Complaint Index (CCI) the Behavior Rating Inventory of Executive Function, adult version (BRIEF-A) and the Beck Depression Inventory, second edition (BDI-II). Twenty-nine participants denied having an mTBI history and 29 reported two or more lifetime mTBIs (range 2-7). Twenty-six participants reported a lifetime history of one mTBI and therefore were excluded from analysis given this study was focused on potential effects of repetitive injuries on cognition and mood. Results: Young otherwise healthy adults with a lifetime history of repetitive mTBI compared to those that reported no history of mTBI reported more change in cognitive functioning over the past five years, worse executive functioning and more symptoms of depression. As the number of lifetime mTBIs increased scores on the CCI, BRIEF-A, and BDI-II also increased, indicating worse functioning. Conclusion: These findings suggest that a lifetime accumulation of two or more mTBIs as compared to a history of no reported mTBIs may result in worse cognitive functioning and symptoms of depression in young adults. Key words: mild traumatic brain injury, neuropsychology, executive function, cognition Word Count: 2,400